การพัฒนาหลักสูตรปรับกรอบความคิดแบบเติบโตในการจัดการเรียนรู้ภาษาอังกฤษ เพื่อการสื่อสารของครู ตามทฤษฎีแห่งตนของดเว็ค: The Development of Curriculum for Changing the Growth Mindset in English Communicative Teaching of English Teachers Based on Dweck’s Self-Theory - Naraporn Sarodom, นราภรณ์ สโรดม (SOCIAL SCIENCES RESEARCH AND ACADEMIC JOURNAL, 2023)
The objective of this study was to develop a curriculum for training English teachers to adopt a growth mindset in communicative English instruction based on Dweck’s Self-Theory. There were four stages of research: 1) studying the mindset of English teachers regarding English communicative teaching and the guideline for changing mindsets in English communicative teaching; 2) creating and checking the quality of the curriculum; 3) studying the outcomes of using this curriculum; and 4) evaluating and enhancing the curriculum. The research sample consisted of 12 primary school English teachers. The research instruments were The English communicative teaching assessment form that the index of item-objective congruence was at 0.60-1.00 and the reliability was at 0.924 and the English communicative teaching ability form that the index of item-objective Congruence was at 0.60-1.00 and the reliability was at 0.868. The experiment lasted for 60 hours. The statistics used for data analysis were ( ), (S.D.), t-test (One sample test), and content analysis for the qualitative data. The research revealed that 1) The English teachers' mindset in English communicative teaching had an average score of 3.01, indicating a mix of growth and fixed mindsets, and that the process of Carol S. Dweck's Self-Theory should be used as a guideline for changing teachers' mindsets. The process of change should be modified to encompass all six mindset characteristics. 2) The curriculum had components: background, principles, objectives, structure, contents, activities, materials, and evaluation, 3) The results of the English teachers' mindset were more growth mindset and less fixed mindset after the implementation of the curriculum, and their scores on the ability to teach English communicatively based on a growth mindset were significantly, at the.01 level, higher than the criteria specified (70%), and 4) The results of evaluating for using the curriculum had an overall of the teachers’ opinions were at highest level, and improvement of the curriculum was the structure of time and a blended model.